Developmental Delay and in Utero Phenytoin Exposure - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Psychomotor development was assessed in preschool children exposed to antiepileptic drugs (AED) in utero as part of a population-based longitudinal follow-up study of children born to women with meticulously treated epilepsy during pregnancy at the Karolinska Institute, Stockholm, Sweden.